Correlation between Knowledge, Attitudes, Nutritional Status and Eating Frequency with Anemia in Young Girls at STIKes Bhakti Pertiwi Indonesia - Rosmiati Rosmiati; Al-Bahra Al-Bahra (JOURNAL EDUCATIONAL OF NURSING(JEN), 2023)
The purpose of this study was to examine the relationship between knowledge, attitudes, nutritional status and eating frequency with anemia in young women at the Bhakti Pertiwi Indonesia STIKes. This research is an analytic survey type with a cross sectional design. The population in this study were all female students of STIKes Bhakti Pertiwi Indonesia, totaling 414 people. Samples were taken as many as 126 respondents, sampling technique with Proportional Random Sampling. Data collection was carried out with primary data using a questionnaire. Data analysis with univariate, bivariate, multivariate. The results of the study showed that 38.9% of respondents experienced anemia. The results of univariate analysis obtained high knowledge (81.0%), positive attitude (50.8%), normal nutritional status (BMI 18.5 - <25.0) of 81.7% and frequency of eating ≥3 times/day ( 55.6%). The results of the bivariate analysis showed that there were four related variables, namely knowledge (p=0.016; OR=3.333), attitude (p=0.049; OR=2.220), nutritional status (p=0.031; OR=3.022), eating frequency (p=0.000; OR=35,282). The results of multivariate analysis showed that factors related to anemia in female adolescents were eating frequency (p=0.000; OR=38.479) while knowledge was the confounding variable. The dominant factor associated with anemia in female adolescents is eating frequency. Eating frequency is a variable associated with anemia in female adolescents. It is suggested to Midwifery student Salsabila Serang to increase the frequency of regular meals 3 times/day with a balanced nutrition menu that is high in iron (Fe).